Long-term supply contracts and collusion in the electricity market - Chloé Le Coq (Stockholm School of Economics, The Economic Research Institute (EFI), 2004)
It has been argued that having a contract market before the spot market enhances competition (Allaz and Vila, 1993). Taking into account the repeated nature of electricity markets, we check the robustness of the argument that the access to contract markets reduces the market power of generators. In particular, we investigate the sensitivity of this result with respect to the finite horizon assumption. This paper proposes a model of the electricity market where firms sign long-term supply contracts with their retailers. Subsequently, the firms repeatedly interact on the spot market. It is shown that contract markets help sustain collusion on the spot market.
Keywords: C72; D43; G13; L13; L94; 330; Contract market; Electricity; Spot Market; Forward; Tacit collusion; Elektrizitätswirtschaft; Markt; Termingeschäft; Kartell; Vertragsrecht